Pendampingan Aparat Desa Dalam Pengelolaan Kopi Liberika Desa Cipasung Kecamatan Darma Kabupaten Kuningan - Thomas Bustomi; Andre Ariesmansyah; Iwan Satibi (Asosiasi Dosen Akuntansi Indonesia, 2022)
Cipasung village, located in Kuningan, West Java, is currently preparing to develop into a tourist village. Cipasung village icon with liberika coffee a which is a tourist attraction, therefore it is necessary to provided assistanced village officials and the village community. This Mentoring Program is believed to be a model for achieving improvement in Cipasung Rintisan Tourism Village Services, especially in the management of Liberika coffee, so that it can increase additional economic income, environmental and respect for the socio- cultural community. The type of tourism that can meet the three criteria above is a form of community- based tourism village. As a result of this mentoring activity, several activities have been carried out such as counseling and training in the field of institutional and community development in Cipasung Village to physical activities such as making and installing road signs to the tourist attraction of Cipasung Village. Assistance in the implementation of the results of counseling and training needs to be carried out until the community can be independent.